Central Banking and Monetary Policy: What will be the post-crisis new normal? - Howard Davies; David Miles; Forrest Capie; Alex Cukierman; Jakob de Haan; Sylvester Eijffinger; Charles Goodhart; Ronald Mahieu; Aleksandra Maslowska-Jokinen; Anna Matysek-Jedrych; Martin Melecki; Bilin Neyapti; et al. (SUERF - The European Money and Finance Forum, 2016)
Central Bankers are currently facing big challenges in designing and implementing monetary policy, as well as with safeguarding financial stability, with the world economy still in the process of digesting the legacy of the crisis. The crisis has changed central banking in many ways: by shifting the focus of monetary policy from fighting too high inflation towards fighting too low inflation; by prompting new `experimental' non-conventional measures, which risk to cause large, long-lasting market distortions and imbalances and which also have more far-reaching distributional consequences than `normal, conventional' monetary policy; and by broadening central banks' responsibilities particularly in the direction of safeguarding banking stability and financial stability at large. This raises several questions for the future: How long will ultra-easy monetary policies last? What are post-crisis growth trajectories, and how will the natural rate of interest rates evolve? How could an exit from ultra-easy monetary policy and a return towards higher nominal interest rates be eventually managed smoothly? Does ultra-easy monetary policy itself affect the economy in a lasting and structural way? Is the pre-crisis economic paradigm governing monetary policy still valid? If not, in what ways should it be adjusted? Are there any reasonable and practical alternatives? Against this background and given the larger post-crisis range of central banks' responsibilities: is the current institutional set-up governing central banks and their relationship to government, Parliament and the financial system still appropriate? What adaptations might be considered? Would they bring an improvement or, on the contrary, a set-back to the unsuccessful policy approaches of the 1960s and 1970s? To discuss these issues, on 14 April 2016 the Baffi Carefin Center (Bocconi University) hosted a SUERF Conference. This introductory chapter aims to provide a framework for the various contributions in this book, and also summarizes some main ideas from later chapters for an overview.
Keywords: E31; E52; E58; G18; 330